Benchmarking medical laboratory performance on a global scale - Huf, Wolfgang; Mohns, Mike; Almeta, Eni; Lister, Rebecca; Buchta, Christoph; Demyanets, Svitlana; Buchberger, Wolfgang; Ettl, Brigitte (Frontiers in Public Health, 2024)
Background and aims Laboratory performance as a relative concept needs repetitive benchmarking for continuous improvement of laboratory procedures and medical processes. Benchmarking as such establishes reference levels as a basis for improvements efforts for healthcare institutions along the diagnosis cycle, with the patient at its center. But while this concept seems to be generally acknowledged in laboratory medicine, a lack of practical implementation hinders progress at a global level. The aim of this study was to examine the utility of a specific combination of indicators and survey-based data collection approach, and to establish a global benchmarking dataset of laboratory performance for decision makers in healthcare institutions. Methods The survey consisted of 44 items relating to laboratory operations in general and three subscales identified in previous studies. A global sample of laboratories was approached by trained professionals. Results were analyzed with standard descriptive statistics and exploratory factor analysis. Dimensional reduction of specific items was performed using confirmatory factor analysis, resulting in individual laboratory scores for the three subscales of “Operational performance,” “Integrated clinical care performance,” and “Financial sustainability” for the high-level concept of laboratory performance. Results and conclusions In total, 920 laboratories from 55 countries across the globe participated in the survey, of which 401 were government hospital laboratories, 296 private hospital laboratories, and 223 commercial laboratories. Relevant results include the need for digitalization and automation along the diagnosis cycle. Formal quality management systems (ISO 9001, ISO 15189 etc.) need to be adapted more broadly to increase patient safety. Monitoring of key performance indicators (KPIs) relating to healthcare performance was generally low (in the range of 10–30% of laboratories overall), and as a particularly salient result, only 19% of laboratories monitored KPIs relating to speeding up diagnosis and treatment. Altogether, this benchmark elucidates current practice and has the potential to guide improvement efforts and standardization in quality & safety for patients and employees alike as well as sustainability of healthcare systems around the globe.